PWE-056 Prospective evaluation of 403 patients with diarrhoea predominant irritable bowel syndrome (D-IBS) fulfilling Rome II criteria. (28th May 2012) - Lin, S; Kurien, M; Leeds, J S; Sanders, D S
Abstract : Introduction: Irritable bowel syndrome (IBS) has a high prevalence with established diagnostic criteria (ROME) used to aid diagnosis. Despite increasing drives to make a positive diagnosis of IBS, patients may still require some investigations to exclude other organic conditions that may present with IBS type symptoms. There has been limited work evaluating diagnostic outcomes in this group of patients. We therefore investigated unselected patients presenting with D-IBS symptoms fulfilling ROME II criteria. Methods: Data were prospectively collected from consecutive patients meeting Rome II criteria for D-IBS in a university hospital. Demographic data, subsequent investigations and diagnostic yields of these tests were collected. All patients underwent haematologic, biochemical and immunologic testing prior to subsequent investigations. The further tests undertaken were at the discretion of the investigating clinician. Statistical analysis was performed using SPSS with Fisher's exact test used to compare categorical data. Results: 403 patients (277 female, median age 52 years) who met Rome II criteria for D-IBS were followed-up during the study period. Investigations undertaken in this cohort of patients were as follows: faecal pancreatic elastase (313) gastroscopy (208), colonoscopy (188), glucose or lactose hydrogen breath tests (62), CT/MRI scan (40), barium enema (38), SeHCAT (18) and small bowel capsule endoscopy (18). Final diagnoses are shown in Abstract PWE-056 table 1 . 88 patients (22%) were subsequently identified to have an alternative diagnosis than D-IBS with pancreatic insufficiency and coeliac disease being the most common. When comparing diagnostic yields of individual tests, a lactose-hydrogen breath test had the highest positive yield of 28.6% (8/28), which was significantly higher than any other diagnostic test undertaken (p<0.01). Conclusion: This study highlights the frequency of investigations undertaken in patients with D-IBS symptoms. While the majority of patients have negative tests, there remains a significant number of patients in whom underlying pathology is identified accounting for their D-IBS symptoms. Although NICE guidelines advocate testing for coeliac disease, our study also demonstrates the importance of testing for pancreatic insufficiency in patients presenting with D-IBS symptoms. Competing interests: None declared.